(untitled) (Journal of Pedagogical Inventions and Practices, 2023)
Idioms are said to mirror the culture of the language. As it happens with most culturally-determined language aspects, idioms pose great difficulties for learners. The study explored the area of idiomatic expressions as being important linguistic units for learners of English as a Foreign Language (EFL). Idiomatic expressions are phrases that consist of two or more words and hence; acquire an idiomatic sense which differ from the literal meaning of the individual words. The study aimed at investigating the role of idiomatic expressions in improving writing and communicative competence and whether these expressions have effective role in improving the students’ performance in language. The study highlighted the important part that idiomatic expressions play in English as a foreign language.